Arctic science education using public museum collections from the University of Alaska Museum: an evolving and expanding landscape - Katherine L. Anderson; Ute Kaden; Patrick S. Druckenmiller; Sarah Fowell; Mark A. Spangler; Falk Huettmann; Stefanie M. Ickert-Bond (Arctic Science, 2017)
Alaska faces unique challenges in STEM (science, technology, engineering, and mathematics) education, including limited accessibility to resources and learning opportunities, and a lack of place-based education resources. Museum education programs, traditionally focused on public outreach through docent-led tours, are playing an increasingly important role in both formal and informal aspects of STEM education to help address these challenges. The University of Alaska Museum (UAM) stands as a model in the Arctic region exemplifying how public natural history museum collections can be utilized to create active place-based learning experiences with the aim of increasing engagement in STEM literacy and building connections between museums and communities. These efforts take many forms, including the development of teaching materials involving physical objects and (or) online data from the open-access database ARCTOS, training preservice teachers, and implementing citizen science projects. Because many UAM specimens and objects are from Alaska, they are easily incorporated into place-based education, thereby demonstrating how the Arctic environment is unique at local and regional scales. Here, we showcase several programs that are either unique to UAM or part of larger national projects and include exemplar teaching modules in order to provide learning opportunities in the Arctic region and other rural settings.